2008
DOI: 10.5089/9781451868692.001
|View full text |Cite
|
Sign up to set email alerts
|

Tax Rate Cuts and Tax Compliance: The Laffer Curve Revisited

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate.The paper shows how tax rate cuts can increase revenues by improving tax compliance. The intuition is that tax evasion has externalities: tax evaders protect each other, because the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 20 publications
0
18
1
1
Order By: Relevance
“…As envisaged during the review of the tax compliance literature, self-employed persons in Ghana could be less tax compliant if there is an increase in the tax rate on their taxable incomes, but could rather declare more incomes if income tax rates are reduced. The only major study that has observed a significant positive relationship between tax rate and tax compliance was by Yitzhaki (1974) and Papp and Takáts (2008), but the current study did not support such findings. The findings of this study are also in line with the self-employed persons" awareness of the prevailing tax rates applicable to them as obtained from the descriptive analysis.…”
Section: Calculating Effect Sizescontrasting
confidence: 99%
“…As envisaged during the review of the tax compliance literature, self-employed persons in Ghana could be less tax compliant if there is an increase in the tax rate on their taxable incomes, but could rather declare more incomes if income tax rates are reduced. The only major study that has observed a significant positive relationship between tax rate and tax compliance was by Yitzhaki (1974) and Papp and Takáts (2008), but the current study did not support such findings. The findings of this study are also in line with the self-employed persons" awareness of the prevailing tax rates applicable to them as obtained from the descriptive analysis.…”
Section: Calculating Effect Sizescontrasting
confidence: 99%
“…In addition, more recent literature has stressed the effect of tax rates on compliance behavior. Of particular relevance in this context is the work of Sanyal, Gang, and Goswami (2000), who show how a Laffer curve may arise under informality, and Papp and Takáts (2008), who focus on the relationship of tax rates, compliance, and revenue yield. 5.…”
Section: Policy Optionsmentioning
confidence: 99%
“…Tax compliance issues are widespread and are of general interest (e.g., Papp and Takáts 2008). The IRS (2006) estimated the federal tax gap, the difference between the amount of tax that taxpayers should pay and the amount that is paid voluntarily and on time, to reach US$345 billion or 16.3% of total revenues in 2001.…”
Section: Income Tax Evasionmentioning
confidence: 99%